AGAMA DAN SPIRIT EKONOMI: STUDI ETOS KERJA DALAM KOMPARASI PERBANDINGAN AGAMA - Wasisto Raharjo Jati (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2018)
This study aimed to analyze relation among religion and economy in developing work ethic. the original thesis concerning relation of religion and work ethic initiated by Max Weber in his study entitled Protestant Ethic and Spirit Capitalism. In Weberian perspective, religion take important role that developing values of work ethics e.g. rationalism, asceticism, and